Pengaruh EPS, ROA, DER Dan PBV Terhadap Harga Saham: Studi Kasus Pada Perusahaan LQ 45 Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2021 - Aprilia Puri Astuti; Erma Setiawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The Indonesian capital market recovered in 2021 after a decline due to the COVID-19 pandemic in 2020. The role of the capital market is crucial for economic growth, and investors need to pay attention to factors such as financial reports and company performance. Investors in LQ45 companies, consisting of 45 stocks with high liquidity, make selections based on transactions and market capitalization. This research focuses on the influence of Earning Per Share (EPS), Return On Assets (ROA), Debt to Equity Ratio (DER), and Price to Book Value (PBV) on the stock prices of LQ45 companies in the period 2018-2021. The research problem involves questions about the influence of each ratio on stock prices. The research objective is to examine the influence of these ratios. The results of the research are expected to provide important information for readers about the factors affecting stock prices and insights for researchers into the dynamics of the capital market. This research can also serve as a reference for further studies. The results of the analysis indicate that Earning Per Share (EPS), Return On Assets (ROA), Debt to Equity Ratio (DER), and Price to Book Value (PBV) significantly influence the stock prices of LQ45 companies.